Gingival Calcifying Epithelial Tumor - A Rare Case Report - Tejasvi, MLA; Bangi, BB; Geetha, P; Pavani, D; Harsha, B (Kathmandu University Medical Journal, 2015)
Calcifying epithelial odontogenic tumors are rare odontogenic neoplasms that account for approximately one percent of all odontogenic tumors. Extra osseous variant is very rare with very few cases being reported in literature Peripheral Calcifying epithelial odontogenic tumor (CEOT) commonly resemble oral hyperplastic or reactive lesions and are histologically similar to their intraosseous counterparts. Here we report a rare case of gingival calcifying epithelial odontogenic tumor in the mandibular posterior region in a 31 year old female patient. Interestingly on literature review in on PubMed search only 22 case reports were available in, English literature, added to that this report will be the 23rd case. Kathmandu University Medical Journal Vol.12(3) 2014; 215-218